CDKL3 Targets ATG5 to Promote Carcinogenesis of Esophageal Squamous Cell Carcinoma - Zhou, Suna; Zhang, Mingxin; Zhou, Chao; Wang, Wei; Yang, Haihua; Ye, Wenguang (Frontiers in Oncology, 2020)
Objective: Our previous study suggested cyclin-dependent kinase-like 3(CDKL3) acts as a new oncogene in ESCC cell line TE-1. However, the molecular mechanisms and biological effects of CDKL3 in esophageal squamous cell carcinoma (ESCC) remain unknown. In the present study, we aimed to explore the clinical significance of CDKL3 in ESCC and how CDKL3 regulates the malignant behavior of ESCC. Methods: ESCC samples were stained by Immunohistochemical staining (IHC) and analyzed for the expression of CDKL3. The functions of CDKL3 on proliferation, apoptosis, migration, invasion, and colony formation were investigated by celigo assay, MTT assay, colony formation, caspase 3/7 activity analysis, transwell migration and invasion assay, respectively. A transplanted tumor model was established to study the functions of FLVCR1 on the tumorigenesis of ESCC cells. Microarray analysis was utilized to identify the CDKL3-regulated genes in ESCC cells. Results: ESCC tumor tissues possessed a significantly higher expression of CDKL3 and autophagy-related gene 5 (ATG5) than matched adjacent normal tissues. The high expressions of CDKL3 were positively associated with the tumor-node-metastasis (TNM) stage and Ki67. Upregulated ATG5 expression was positively correlated with male, advanced tumor(T) stage, and TNM stage. Kaplan-Meier analysis showed that ESCC patients with higher expression of CDKL3 or ATG5 had a shorter overall survival. The worst prognosis was recognized in patients with both high manifestations of CDKL3 and ATG5. Time-dependent receiver operating characteristic (ROC) curve was established to reveal that the combination of CDKL3, ATG5 and TNM stage–based model had better prognostic accuracy than TNM stage. Moreover, CDKL3 knockdown markedly repressed cell growth and aggressivity in vitro and vivo. Mechanistically, ATG5 was confirmed as a downstream gene involved in the pro-oncogenic function of CDKL3. Conclusion: CDKL3 can be utilized as an independent poor prognostic marker in ESCC patients. Furthermore, CDKL3 may promote tumor profession, invasion, metastasis, and prohibit tumor apoptosis partly by ATG5 activation.